Influence of the geometry of fluorescently labelled DNA constructs on fluorescence anisotropy assay - Brom, Tomas; Reddavide, Francesco V; Heiden, Stephan; Thompson, Michael; Zhang, Yixin (Biochemical and biophysical research communications, 2020)
DNA-encoded chemical libraries (DECLs) are powerful tools for modern drug discovery. A DECL is a pooled mixture of small molecule compounds, each of which is tagged with a unique DNA sequence which functions as a barcode. After incubation with a drug target and washing to remove non-binders, the bound molecules are eluted and submitted for DNA sequencing to determine which molecules are binding the target. While the DECL technology itself is ultra-high throughput, the following re-synthesis of identified compounds for orthogonal validation experiments remains the bottleneck. Using existing DNA-small molecule conjugates directly for affinity measurements, as opposed to complete compound resynthesis, could accelerate the discovery process. To this end, we have tested various geometries of fluorescently-labelled DNA constructs for fluorescence anisotropy (FA) experiments. Minimizing the distance between the fluorescent moiety and ligand can maximize the correlation between ligand-protein interaction and corresponding change in fluorophore rotational freedom, thus leading to larger, easier to interpret changes in FA values. However, close proximity can also cause artifacts due to potentially promiscuous interactions between fluorophore and protein. By balancing these two opposite effects, we have identified applicable fluorescently labelled DNA constructs displaying either a single ligand or pairs of fragments for affinity measurement using a FA assay.
Keywords: Fluorescent Dyes; vazebná místa; Small molecules; Fluorescence Polarization; Hit validation; fluorescenční polarizace; DNA; techniky kombinatorické chemie; Drug Evaluation, Preclinical; fluorescenční barviva; Small Molecule Libraries; Ligands; preklinické hodnocení léčiv; Fluorescence anisotropy; DNA-Encoded chemical library; Drug Discovery; Combinatorial Chemistry Techniques; knihovny malých molekul; Drug discovery; objevování léků; ligandy; Binding Sites